(untitled) (Journal of Social Sciences Review, 2025)
This study investigates the impact of Career Capital, Joint Responsibility, Career Management, Career Planning, and Career Opportunity on Career Success, with a particular focus on the moderating effect of Employee behaviour. The study integrates career capital (skills, knowledge, networks) with joint responsibility between employers and employees and determine how these elements help advance careers. It also highlights how career management practice and the presence of career opportunities shape one’s career success. A study based on primary quantitative data from banking sector employees shows how gaps in existing literature about how these variables are connected should be filled and that employee behaviour is important in the enhancement of others’ career outcomes. The data has been collected from a sample of 150 from the HR professional targeted population. The Smart PLS software has been used to analyse the data and conduct the operations. Our findings can be useful to organizations that are trying to develop talent management strategies, wherein we highlight that it is essential for such organizations to put a collaborative supportive environment in place and one that is evaluating talent, career planning, skill development, career growth.